Problematika Pengakuan Tanah Ulayat Masyarakat Minangkabau dalam Perspektif Hukum Administrasi Negara serta Disharmonisasi Regulasi - Frans Tory Damara Tory Damara Pradipta (Universitas Sultan Ageng Tirtayasa, 2026)
This study examines the issues surrounding the recognition of ulayat land (customary land) of the Minangkabau people from the perspective of state administrative law, which is characterized by a mismatch between social recognition within customary law and formal recognition within administrative state law. This condition creates legal uncertainty and the potential for conflict in the management of ulayat land. The study aims to analyze the forms of regulatory disharmony and their implications for the recognition of ulayat land. The research employs a normative legal method with statutory and conceptual approaches, using primary and secondary legal materials analyzed qualitatively. The findings show that the recognition of ulayat land still faces challenges such as overlapping regulations, complex administrative procedures, and the dominance of state law over customary law. These conditions result in weak legal certainty and suboptimal protection for indigenous communities. Therefore, regulatory harmonization and strengthening of administrative mechanisms are needed to ensure more effective recognition of ulayat land in accordance with the characteristics of the Minangkabau society.